EARLY DIAGNOSIS AND PREVENTION OF CARDIOVASCULAR DISEASES AMONG WOMEN OF WORKING AGE WORKING IN HEALTHCARE INSTITUTIONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Cardiovascular diseases (CVD) are the main cause of death and disability in the 21st century throughout the world. People with CVD or at high risk need early identification and care. Most cardiovascular diseases can be prevented by addressing risk factors such as unhealthy diet and obesity, physical inactivity, tobacco use, physical inactivity and harmful use of alcohol through population-based strategies.